Assessment of Protected area Management effectiveness of Sikkim, Eastern Himalaya, India - Ansari, Nasim Ahmad; Bhardwaj, Anil Kumar; Srivastava, Ajay (Indian Forester, 2020)
Globally protected areas (PAs) are considered as the cornerstones of biodiversity conservation. In recent years, there has been a growing concern among PA professionals to assess the management effectives o f PAs. The present study has been carried out for the evaluation o f PAs of Sikkim by applying IUCN Protected Area Management Effectiveness (PAME) framework with little modifications. There are eight PAs in Sikkim, which have been evaluated through this process during 2014-2015. The resultindicates thatPAs ofSikkim have an overall average evaluation score of55%, Khangchendzonga National Park being the highest score o f 62.50% and FambongLho Wildlife Sanctuary being the lowest score o f 46.67%. Four PAs o f the state are rated in ’good’ category and remaining four are rated in ’fair’ category. This exercise reveals that PA Network of the state is better placed as far as community support, protection, human wildlife conflicts and landscape integration are concerned. However, quality o f management plans and capacity o f field staff for wildlife management are critical areas which need to be addressed on a priority basis. The study provides an insight about strengths and weaknesses of the management and possible ways forimprovement o fPAs. The study also tries to look at the overall issues ofPA management and what policy level and institutional reforms are needed to strengthen the biodiversity conservation initiatives o f the State.